Genotoxicity assessment of piperitenone oxide: An in vitro and in silico evaluation. (August 2017) - Di Sotto, Antonella; Di Giacomo, Silvia; Abete, Lorena; Božović, Mijat; Parisi, Olga A.; Barile, Fabio; Vitalone, Annabella; Izzo, Angelo A.; Ragno, Rino; Mazzanti, Gabriela
Abstract: Piperitenone oxide, a natural flavouring agent also known as rotundifolone, has been studied for the genotoxicity assessment by an integrated in vitro and in silico experimental approach, including the bacterial reverse mutation assay, the micronucleus test, the comet assay and the computational prediction by Toxtree and VEGA tools. Under our experimental conditions, the monoterpene showed to induce both point mutations (i.e. frameshift, base-substitution and/or oxidative damage) and DNA damage (i.e. clastogenic or aneuploidic damage, or single-strand breaks). Computational prediction for piperitenone oxide agreed with the toxicological data, and highlighted the presence of the epoxide function and the α, β-unsaturated carbonyl as possible structural alerts for DNA damage. However, improving the toxicological libraries for natural occurring compounds is required in order to favour the applicability of in silico models to the toxicological predictions. Further in vivo evaluations are strictly needed in order to evaluate the role of the bioavailability of the substance and the metabolic fate on its genotoxicity profile. To the best of our knowledge, these data represent the first evaluation of the genotoxicity for this flavour compound and suggest the need of further studies to assess the safety of piperitenone oxide as a flavouring agent. Graphical abstract: Highlights: An integrated in vitro and in silico genotoxicity assessment for the natural flavouring agent piperitenone oxide. Experiments carried out in vitro by Ames test, micronucleus and comet assays, and i n silico by Toxtree and VEGA tools. Test substance induced point mutations and DNA damage, including micronuclei and single-strand breaks. Epoxide and α, β-unsaturated carbonyl found as structural alerts for mutagenicity at computational analysis.